THE CRITICAL THINKING ABILITY OF STUDENT WITH LOW PRIOR KNOWLEDGE WHO LEARN USING PROBLEM BASED LEARNING - Ni Made Intan Kertiyani; Ketut Sarjana; Ulfa Lu'luilmaknun (MATEMATIKA DAN PEMBELAJARAN, 2023)
In the twenty-first century, having an ability for thinking critically is essential. Students, including those with low prior knowledge in mathematics, are expected to have this ability. Therefore, the purpose of this study is to evaluate students' critical thinking abilities when they first start using PBL (Problem Based Learning). This study uses a qualitative approach. The research subjects consisted of two mathematics education students who were repeating lectures. The research instrument consisted of tests of critical thinking skills and interviews. The results obtained are indicators of critical thinking skills that appear well in students with low initial abilities is the interpretation of the indicators. As for the analysis of indicators, applying the solutions obtained, making inferences and concluding the results appear at an unfavorable level. These results indicate that students with low prior knowledge who study using PBL still have a low level of critical thinking.